Characteristics of Intrapreneurs in Scale-Intensive Service Firms - Katja Maria Hydle; Tor Helge Aas; Karl Joachim Breunig (Journal of Entrepreneurship, Management and Innovation)

(untitled)
This empirical paper explores the work of employees in charge of service innovation when firms develop and launch new scale-intensive services by addressing two re- search questions: i) How do employees responsible for service innovation work? and ii) what are the related managerial implications when developing and launching new scale-intensive services? To this end, 21 qualitative, in-depth interviews were con- ducted with employees in five large scale-intensive service firms. The findings suggest that the involvement of internal professionals is an asset when new scale-intensive services are developed, and that internal professionals act as intrapreneurs when they are involved in the development of radically new scale-intensive services. This paper integrates understanding from the innovation management literature with knowledge of professionals from extant literature on professional service firms since we find that professionals in scale-intensive firms act as intrapreneurs. Thus, this pa- per extends the theory on determinants of innovation in scale-intensive service firms, blending insights from both findings and theory.